Odpowiedzi

2010-01-05T16:45:56+01:00
Metodą podstawiania

x+y=2
y-2x=3

y=2-x
2-x-2x=3

y=2-x
-3x=1 |:-3

y=2-x
x=-⅓

y=2-(-⅓)
y=2⅓



x+y=4
y-2x=-2

y=4-x
4-x-2x=-2

y=4-x
-3x=-6 |:-3

y=4-x
x=2

y=4-2
y=2
Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-05T17:20:25+01:00
1.
Metoda podstawiania
( x + y = 2
( y - 2x = 3

( y = 2 - x
( 2 - x - 2x = 3

( y = 2 - x
( - x - 2x = 3 - 2

( y = 2 - x
( - 3x = 1 /:(-3)

( y = 2 - x
( x = -⅓

( y = 2 + ⅓
( x = -⅓

( x = -⅓
( y = 2⅓

Metoda przeciwnych współczynników
( x + y = 2
( y - 2x = 3

( x + y = 2 /*2
( -2x + y = 3

( 2x + 2y = 4
( -2x + y = 3
___________

2x - 2x + 2y + y = 4 + 3
3y = 7 /: 3
y = 2⅓

x + y = 2
x = 2 - y
x = 2 - 2⅓
x = -⅓

( x = -⅓
( y = 2⅓

2.
Metoda podstawiania
( x + y = 4
( y - 2x = -2

( y = 4 - x
( 4 - x - 2x = -2

( y = 4 - x
( - x - 2x = -2 - 4

( y = 4 - x
( - 3x = -6 /:(-3)

( y = 4 - x
( x = 2

( y = 4 - 2
( x = 2

( x = 2
( y = 2

Metoda przeciwnych współczynników
( x + y = 4
( y - 2x = -2

( x + y = 4 /*2
( - 2x + y = -2

( 2x + 2y = 8
( - 2x + y = -2
____________

2x - 2x +2y + y = 8 - 2
3y = 6 /:3
y = 2

x + y = 4
x = 4 - y
x = 4 - 2
x = 2

( x = 2
( y = 2